Siderophore-Mediated Iron Acquisition Plays a Critical Role in Biofilm Formation and Survival of Staphylococcus epidermidis Within the Host - Oliveira, Fernando; Lima, Tânia; Correia, Alexandra; Silva, Ana Margarida; Soares, Cristina; Morais, Simone; Weißelberg, Samira; Vilanova, Manuel; Rohde, Holger; Cerca, Nuno (Frontiers in Medicine, 2021)
Iron acquisition through siderophores, a class of small, potent iron-chelating organic molecules, is a widely spread strategy among pathogens to survive in the iron-restricted environment found in the host. Although these molecules have been implicated in the pathogenesis of several species, there is currently no comprehensive study addressing siderophore production in S. epidermidis. S. epidermidis is an innocuous skin commensal bacterium. The species, though, has emerged as a leading cause of implant-associated infections, significantly support by an inherent ability to form biofilms. The process of adaptation from skin niche environments to the hostile conditions during invasion is yet not fully understood. Herein, we addressed the possible role of siderophore production in S. epidermidis virulence. We first identified and deleted a siderophore homologue locus, sfaABCD, and provided evidence for its involvement in iron acquisition. Our findings further suggested the involvement of siderophores in the protection against oxidative stress-induced damage and demonstrated the in vivo relevance of a siderophore-mediated iron acquisition during S. epidermidis infections. Conclusively, this study addressed, for the first time in this species, the underlying mechanisms of siderophore production, highlighting the importance of a siderophore-mediated iron acquisition under host relevant conditions and, most importantly, its contribution to survival within the host.